INTERNATIONAL PRACTICE OF SUPERVISING ACTIVITIES OF FINANCIAL (CREDIT) COOPERATIVES THROUGH SELF-GOVERNMENT MECHANISMS - Хоружий , Сергій (Socio-economic relations in the digital society, 2019)
This article contains the researches on the examples of effective performance of self-government functions by financial institutions, which also create financial infrastructure for the financial (credit) cooperatives. It has been proven that association of credit unions cannot independently carry out all spectrum of self-government functions. Legislative innovations that allow to carry out self-government functions for joint credit unions and functions of the financial center of credit co-operation have been also proposed in this article.
Keywords: financial (credit) cooperative; credit union; association; self-government; self-regulatory organization; financial institution